(873) A multi- channel queuing model: A Simulation Approach نموذج قائمة انتظار متعددة القنوات: نهج محاكاة - AlWalid ElShafei. (INP, 2024)
The problem describes a model for a manufacturing facility producing a product consisting of three components, each produced in separate processes characterized by stochastic process times. The time intervals between order arrivals at the facility are random variables. When a new order arrives, process times for each of the three processes are generated according to a specific distribution. The product is assembled once all three components are completed, allowing the facility to accept a new order. A new order cannot be accepted until all components of the previous order are finished and all processes are vacant. If the processes are not available, new orders are placed in a waiting line until the facility is freed up.